Psychometric validation of the Brazilian Version of the Pet Attachment Questionnaire (PAQ): An examination of predictors of attachment styles among cat owners - Luchesi, Suzana Helena; Machado, Daiana Souza; Trindade, Pedro Henrique Esteves [UNESP]; Mikulincer, Mario; Otta, Emma (Elsevier, 2022)
It is important for researchers of human-animal relationships to have access to research instruments validated in their original languages, as sociocultural and linguistic semantic variations can interfere with the answers. Our objectives were to: (i) validate the Brazilian version of the Pet Attachment Questionnaire (PAQ) among cat owners; (ii) study individual differences in avoidant and anxious attachment as a function of respondents’ sociodemographic characteristics and the Satisfaction With Life Scale (SWLS); (iii) investigate relationships between PAQ dimensions and attachment intensity using the Lexington Attachment to Pets Scale (LAPS). Information from 301 Brazilian cat owners was collected. After evaluating internal consistency, a principal component analysis was conducted to examine the factorial structure of scale. In addition, we conducted multiple linear model (MLM) and hierarchical cluster analysis to further explore attachment patterns. Three items were excluded. After exclusion, results presented better indicators. The Brazilian 23-items PAQ version showed adequate psychometric properties and the same two-dimensional structure (avoidance and anxiety) as the English version. MLM indicated that male gender, having children, younger age, and lower LAPS scores were significant predictors of higher avoidant attachment; while not having children and higher LAPS were significant predictors of higher anxious attachment. The dendrogram of hierarchical clustering revealed three distinguishable groups of human-pet attachment: avoidant profile, anxious profile, and secure profile. The Brazilian 23-items PAQ version is recommended for use in the Brazilian population both for research purposes and for applied purposes considering its internal consistency, structure, validity, simplicity, and practicality.
Keywords: Attachment; Cat owners; Human-cat relationship